The Rise of Institutional Islamists and the Prospects of Democracy with Special Reference to the Middle East (Journal of Social Sciences Review, 2024)
The Middle East presents a democratic dilemma for the West as they have to choose between what the world calls the ruling autocrats and religious theocrats opposing them. There are some in the Western world who believe that Institutional Islamists can be made partners in the democratization process. They believe that they are more moderate democrats in their approach as they take part in elections and are willing to be part of the democratic institutions. As democracy is more than just contesting elections, the big question is if institutional Islamists can be a viable alternative to the ruling autocrats in the ME. This article will discuss this question in more detail to reach an informed and holistic conclusion.
Keywords: Institutional Islamist; Democracy; Middle East; Western World; Election